2015
DOI: 10.1016/j.ijsu.2015.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and body composition after laparoscopic sleeve gastrectomy in men: A short-term longitudinal study

Abstract: After LSG, body size and variables related to body composition (except for TB BMC) decreased with an accompanying decrease in FN BMD in the men in this study. Spine BMD increased, and TB BMD did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
5
20
1
2
Order By: Relevance
“…Nevertheless, most studies on SG reported decreased BMD ( Maghrabi et al, 2015 ; Carrasco et al, 2014 ; Vilarrasa et al, 2013 ; Muschitz et al, 2016 ; Hsin et al, 2015 ; Muschitz et al, 2015 ; Pluskiewicz et al, 2012 ; Adamczyk et al, 2015a ), whereas two studies described an opposite trend with increased BMD ( Adamczyk et al, 2015b ; Ruiz-Tovar et al, 2013 ). A possible explanation for this discrepancy is that Adamczyk et al investigated solely men, and this observation might indicate sex-dependent responses ( Adamczyk et al, 2015b ).
Fig.
…”
Section: Effect Of Bariatric Surgery On Bmd and Fracturesmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, most studies on SG reported decreased BMD ( Maghrabi et al, 2015 ; Carrasco et al, 2014 ; Vilarrasa et al, 2013 ; Muschitz et al, 2016 ; Hsin et al, 2015 ; Muschitz et al, 2015 ; Pluskiewicz et al, 2012 ; Adamczyk et al, 2015a ), whereas two studies described an opposite trend with increased BMD ( Adamczyk et al, 2015b ; Ruiz-Tovar et al, 2013 ). A possible explanation for this discrepancy is that Adamczyk et al investigated solely men, and this observation might indicate sex-dependent responses ( Adamczyk et al, 2015b ).
Fig.
…”
Section: Effect Of Bariatric Surgery On Bmd and Fracturesmentioning
confidence: 94%
“…It is, however, important to note that at this moment the studies on SG are still limited, both in terms of duration of follow-up and sample size ( Maghrabi et al, 2015 ; Carrasco et al, 2014 ; Vilarrasa et al, 2013 ; Muschitz et al, 2016 ; Hsin et al, 2015 ; Muschitz et al, 2015 ; Pluskiewicz et al, 2012 ; Adamczyk et al, 2015a ; Adamczyk et al, 2015b ; Ruiz-Tovar et al, 2013 ). Nevertheless, most studies on SG reported decreased BMD ( Maghrabi et al, 2015 ; Carrasco et al, 2014 ; Vilarrasa et al, 2013 ; Muschitz et al, 2016 ; Hsin et al, 2015 ; Muschitz et al, 2015 ; Pluskiewicz et al, 2012 ; Adamczyk et al, 2015a ), whereas two studies described an opposite trend with increased BMD ( Adamczyk et al, 2015b ; Ruiz-Tovar et al, 2013 ). A possible explanation for this discrepancy is that Adamczyk et al investigated solely men, and this observation might indicate sex-dependent responses ( Adamczyk et al, 2015b ).…”
Section: Effect Of Bariatric Surgery On Bmd and Fracturesmentioning
confidence: 99%
“… 13 The results on the changes in BMD after LSG are inconsistent. 14 18 It has been shown that femoral neck BMD decreases, spine BMD increases, and total body BMD remains unchanged in men with obesity after LSG, 14 while another study has shown that BMD increases during the first and second years after LSG. 15 In addition, researchers have found that BMD decreases after LSG, 16 – 18 and the effect of LSG on BMD differs between genders, decreasing significantly in females while remaining unchanged in males.…”
Section: Introductionmentioning
confidence: 99%
“…B/M surgery represents the most effective therapeutic tool for morbid obesity and a promising approach towards obesity-related comorbidities, because, unlike conservative treatment, it assures significant, quick and relatively sustainable weight loss [19,[22][23][24]. Although this effect is predominantly based on the desirable fat mass reduction, it may also be associated with a decrease of other body components, such as muscles and bones [10,19,20]. Both obesity and sarcopenia increase health-related risks, especially when they co-exist.…”
Section: Discussionmentioning
confidence: 99%
“…DEXA measurements were performed before and 24 months after the B/M procedure using the Hologic Discovery A densitometer (Mississauga, Ontario, Canada), calibrated according to the manufacturer's recommendations. The precision error and coefficient of variation were established, which allowed the value of the minimal significant change to be calculated as described in previous studies [18][19][20]. Recorded measurements included fat mass index (FMI) -a measure of relative fat content, independent of fat free mass, estimated visceral adipose tissue (Est VAT) -estimated amount of visceral fat, lean mass index (LMI) -a measure of relative lean content, independent of fat mass, appendage lean mass index (ALMI) -a measure of relative lean mass in arm and legs, bone mineral content (BMC), Z score -for patients aged under 50 and T score -for those above 50 as measures of osteoporosis.…”
Section: Methodsmentioning
confidence: 99%